Photoenhanced excitonic correlations in a Mott insulator with nonlocal interactions - Bittner, Nikolaj; Golež, Denis; Eckstein, Martin; Werner, Philipp (Physical Review B, 2020)
We investigate the effect of nonlocal interactions on the photodoped Mott insulating state of the two-dimensional Hubbard model using a nonequilibrium generalization of the dynamical cluster approximation. In particular, we compare the situation where the excitonic states are lying within the continuum of doublon-holon excitations to a setup where the excitons appear within the Mott gap. In the first case, the creation of nearest-neighbor doublon-holon pairs by excitations across the Mott gap results in enhanced excitonic correlations, but these excitons quickly decay into uncorrelated doublons and holons. In the second case, photoexcitation results in long-lived excitonic states. While in a low-temperature equilibrium state, excitonic features are usually not evident in single-particle observables such as the photoemission spectrum, we show that the photoexcited nonequilibrium system can exhibit in-gap states associated with the excitons. The comparison with exact-diagonalization results for small clusters allows us to identify the signatures of the excitons in the photoemission spectrum.
CRIS-Team Scopus Importer:2020-03-06